2012
DOI: 10.1002/app.38524
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanocrystals extracted from okra fibers in PVA nanocomposites

Abstract: Cellulose nanocrystals (CNC) were extracted from okra bahmia (Abelmoschus Esculentus) bast fibers and inserted in different tenors (1, 2, 5, and 10 wt %) as the reinforcement of a poly(vinyl alcohol) (PVA) matrix. The extraction of cellulose was carried out in a two-step procedure: the first chemical treatment led to the production of holocellulose by the gradual removal of lignin, while the subsequent sulphuric acid hydrolysis process allowed obtaining cellulose nanocrystals in an aqueous suspension. The disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(72 citation statements)
references
References 53 publications
5
67
0
Order By: Relevance
“…Similar behavior was found for other PVA-CNC composites. 23,45,46 These results indicate that the thermal properties of PVA are not degenerated by the addition of CNCs, however, the presence of CNCs can slow down the degradation of PVA. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Examples of WAXD diffractograms of PVA films are presented in Figure 9a.…”
Section: Preparation Of Rcncsmentioning
confidence: 85%
“…Similar behavior was found for other PVA-CNC composites. 23,45,46 These results indicate that the thermal properties of PVA are not degenerated by the addition of CNCs, however, the presence of CNCs can slow down the degradation of PVA. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Examples of WAXD diffractograms of PVA films are presented in Figure 9a.…”
Section: Preparation Of Rcncsmentioning
confidence: 85%
“…There was noticeable improvement in tensile properties with tensile modulus showing a four to five times improvement over neat PVA. Fortunati et al (2012) reported that a 5 wt% cellulose content proved ideal to promote a direct mechanical interaction between the PVA and CNC. Zimmerman et al (2004) reported up to three times higher tensile modulus and up to five times higher tensile strength containing 20 wt% MCF in PVA.…”
Section: Poly(vinyl Alcohol) Pvamentioning
confidence: 98%
“…Though it contains higher percent of cellulose, it may have potentiality to make good-quality composite with thermoplastic/ thermoset resins. Fortunati et al (2013) prepared OBF-PVA composites and studied its degradation properties. The fibres possess good mechanical properties and biodegradable characteristics.…”
Section: Introductionmentioning
confidence: 99%